Efektivitas Metode Problem Solving Terhadap Hasil Belajar Matematika pada Materi Volume Kubus dan Balok Siswa SD Islam Al Hikmah Samarinda - Tri Lidya Octaviani; Abdul Razak; Maulida Ulfa Hidayah; Khonsaullabibah Maisun Nur Rifdah; Toni; Hilda Hamzah (NOVARA: Nusantara Innovation and Educational Technology, 2024)
This research aims to determine effective problem solving methods on mathematics learning outcomes on the volume of cubes and blocks for class V students at Al Hikmah Islamic Elementary School, Samarinda. This research is experimental research with a quasi-experimental design. The population and sample used were all class V students at Al Hikmah Islamic Elementary School, Samarinda, totaling 75 people. The experimental group was class V Yaqub and the control group was class V Ishaq. Learning outcome data was collected using pretest and posttest in the form of essay questions. The results obtained from this research are that the problem solving method is effectively used in mathematics subjects on the volume of cubes and blocks at Al Hikmah Islamic Elementary School, Samarinda. This is based on the hypothesis test calculation using the Z test to obtain a significance value of 0.015<0.05, which means H0 is rejected and H1 is accepted. This means that there is a difference in learning outcomes by applying problem solving methods and conventional methods. It can be concluded that the problem solving method is effective on mathematics learning outcomes on the volume of cubes and blocks for class V students at Al Hikmah Islamic Elementary School, Samarinda.